A new approach to the extragradient method for nonlinear variational inequalities - Verma Ram U (Journal of Inequalities and Applications, 2000)
The approximation-solvability of the following nonlinear variational inequality (NVI) problem is presented: Determine an element such that where is a mapping from a nonempty closed convex subset of a real Hilbert space into . The iterative procedure is characterized as a nonlinear variational inequality (for any arbitrarily chosen initial point ) which is equivalent to a double projection formula where denotes the projection of onto .